Planning the Islamic Education Learning Process: A Case Study At MI Khoeru Ummah Bogor: Perencanaan Proses Pembelajaran Pendidikan Islam: Studi Kasus Di MI Khoeru Ummah Bogor - Wahyuni, Selvi Sri; Mujahidin, Endin; Fatryani, Ariqo; Alam, Muhammad Fahrul (Civilization Research: Journal of Islamic Studies, 2024)
This study aims to find out how the role of The Principal in planning and evaluating in achieving educational goals, especially in the learning process of Islamic Religious Education. Researchers have conducted qualitative research using interview, observation, and documentation techniques. An interview has been conducted with the Principal of MI Khoeru Ummah Bogor where observations were made by focusing on activities related to learning planning and evaluation of Islamic education learning planning at MI Koeru Ummah Bogor.The results of the research conducted show that the importance of The Principal as a leader of educational institutions planning and evaluating learning in his institution to be able to improve the quality of education. Then the Principal has a very important role in achieving the learning objectives to be achieved, especially outputs that have quality and competence that meet expectations in improving the quality of Islamic Religious Education.